Improving the Algorithm for the Management of Patients with Viral Hepatitis Using Contrast-Free Hepatic Arterial Spin Labelling Magnetic Resonance Perfusion - E. N. Simakina; T. G. Morozova (Вестник рентгенологии и радиологии)
Objective: improving the algorithm for the management of patients with viral hepatitis using contrast-free arterial spin labelling (ASL) magnetic resonance (MR) perfusion.Material and methods. A total of 116 patients with viral hepatitis (VH) B, C and B + C were examined on the basis of Clinical hospital No. 1 (Smolensk): 75 (64.7%) men and 41 (35.3%) women, mean age 49.7 ± 2.3 years. The patients underwent instrumental diagnostic methods: ultrasound, clinical elastography, contrast-free hepatic ASL MR perfusion. Liver biopsy (n = 57) was used as the reference method.Results. The results of ASL MR perfusion had a high correlation with the data of clinical elastography in the diagnosis of fibrotic process; the diagnostic and prognostic significance of ASL liver perfusion in the diagnosis of fibrotic process was: AUROC 0.943 (95% CI, 0.884–0.953). There was a high correlation between ASL MR perfusion with Doppler ultrasound of hepatic blood vessels in the diagnosis of arterial blood flow disorders, but in VH В + C and cirrhosis – diagnostic and prognostic significance of the method: AUROC 0.951 (95% CI 0.932–0.972).Conclusion. ASL MR perfusion in VH patients allows to predict fibrotic changes in the hepatic parenchyma (AUROC 0.934 (95% CI 0.845–0.957)), provides information about changes in blood flow in the parenchymal structure (p < 0.005). The algorithm for the examination of VH patients should include contrast-free ASL MR perfusion at admission (AUROC 0.865 (95% CI 0.843–0.928)) and in dynamic follow-up (AUROC 0.915 (95% CI 0.881–0.946)).